Environmental enrichment strategies for weaned pigs: Welfare and behavior - Vargas, Larissa Braganholo; Caldara, Fabiana Ribeiro; Lippi, Isabella Cristina de Castro; de Oliveira, Geyssane Farias [UNESP]; Odakura, Agnês Markiy; Burbarelli, Maria Fernanda de Castro; Garcia, Rodrigo Garófallo; Almeida Paz, Ibiara Correia de Lima [UNESP]; dos Santos, Luan Sousa (Taylor & Francis, 2021)
This research aims to evaluate the effects of different types and strategies of environmental enrichment for weaned pigs on behavior. Forty weaned piglets aged 21 to 28 days were distributed in a completely randomized design in five treatments: without enrichment object, full-time cognitive enrichment, intermittent cognitive enrichment, alternate cognitive and sensory enrichment every 24 hours, and alternate cognitive and sensory enrichment every 48 hours. Behavioral observations were made for 15 days considering pig as experimental unit. Pigs of control and continuous cognitive enrichment treatments were submitted to human approach test, novel arena test, and novel object test. Pigs kept in an unstimulated environment show a higher frequency of unwanted behaviors compared to pigs in other treatments regardless of enrichment type. Pigs with alternation of enrichment type every 24 hours showed a longer interaction time with enrichment objects. Enrichment objects in rearing environment during nursery phase reduced undesirable behaviors and reactivity to unknown situations. Strategies such as alternating the type of enrichment every 24 or 48 hours are effective in maintaining the novelty and the animals’ interest.
Keywords: Cognitive enrichment; neophobia; piglets; weaning; well-being